The coming and going of "come" and "go"; Multi-verb directional motion constructions in Surinamese Javanese - Villerius, Sophie (Wacana, Journal of the Humanities of Indonesia, 2021)
This article examines multi-verb directional motion constructions in Surinamese Javanese, a heritage language undergoing structural influence from Dutch and Sranantongo. These are constructions which express 'direction away' by means of a V2 lunga 'go away'. They are more frequent - and used with more different V1s - than in Indonesian Javanese, the baseline. The frequency change is a pattern change, a result of cross-linguistic transfer from Sranantongo, in which multi-verb constructions to express 'direction away' are very frequent. The extension of the usage contexts to more V1s is a form of semantic extension, and it is the first stage of contact-induced grammaticalization. This is caused by entrenchment of the schema motion verb + away, which exists in both Dutch and Sranantongo. The meaning of the constructions is also changing: whereas in Indonesian Javanese the directional element never refers to the causee alone, it frequently does in Surinamese Javanese. Finally, some preliminary observations are made with respect to the possible development of a parallel construction expressing 'direction towards' with V2 teka 'come', modeled on the Sranantongo multi-verb constructions with V2 kon 'come'.